2004
DOI: 10.1007/s00134-004-2463-6
|View full text |Cite
|
Sign up to set email alerts
|

Sustained moderate reductions in arterial CO2 after brain trauma Time-course of cerebral blood flow velocity and intracranial pressure

Abstract: Objective: In healthy volunteers cerebral blood flow starts to recover towards baseline within a few minutes of continued hyperventilation due to normalisation of perivascular pH. We investigated the timecourse of changes in middle cerebral artery mean flow velocity (FVm) and intracranial pressure (ICP) in head-injured patients during sustained moderate reductions in arterial partial pressure of CO 2 (PaCO 2 ). Design: Observational study. Patients: Twenty-seven sedated, mechanically ventilated patients with s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
1
2

Year Published

2005
2005
2021
2021

Publication Types

Select...
6
4

Relationship

2
8

Authors

Journals

citations
Cited by 44 publications
(21 citation statements)
references
References 25 publications
0
18
1
2
Order By: Relevance
“…CO 2 is known as a major factor affecting the ICP, even in patients with moderate to severe head injury [19]. ICP monitoring in association with CO 2 can be effective in appropriate management of mechanically ventilated patients in intensive care unit, as well as intraoperative period.…”
Section: Discussionmentioning
confidence: 99%
“…CO 2 is known as a major factor affecting the ICP, even in patients with moderate to severe head injury [19]. ICP monitoring in association with CO 2 can be effective in appropriate management of mechanically ventilated patients in intensive care unit, as well as intraoperative period.…”
Section: Discussionmentioning
confidence: 99%
“…There are no data to support the targeting of a specific PaCO 2 after resuscitation from cardiac arrest; however, extrapolation of data from studies of other cohorts suggest ventilation to nor-mocarbia is appropriate. Studies in brain-injured patients have shown that the cerebral vasoconstriction caused by hyperventilation may produce potentially harmful cerebral ischaemia (Muizelaar et al, 1991;Steiner et al, 2004;Coles et al, 2007). Hyperventilation also increases intratho-racic pressure, which will decrease cardiac output both during and after CPR (Aufderheide et al, 2004;Aufderheide and Lurie, 2004).…”
Section: Ventilationmentioning
confidence: 96%
“…An important recent finding of Steiner et al [27 ], who measured CBF velocity in 27 head injured patients during sustained moderate hyperventilation, was that following onset of hyperventilation, reduction in CBF continues for longer in patients with head injury than in healthy volunteers. Moreover, ICP values return to baseline sooner than flow velocity, suggesting that potentially harmful reductions in CBF may persist beyond the useful period of ICP reduction.…”
Section: Monitoring Cerebral Blood Flowmentioning
confidence: 95%